Visionary leadership and teacher learning innovation: a literature review on the mediating roles of teacher welfare, professional collaboration, and work motivation - Six Meredo; Rambat Nur Sasongko; Muhammad Kristiawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study aims to synthesize empirical evidence on how visionary leadership of school principals contributes to teacher learning innovation, with a specific focus on the mediating roles of teacher welfare, professional collaboration, and work motivation. This study employed a systematic literature review approach by analyzing relevant studies indexed in Scopus, ERIC, Google Scholar, and Indonesian national journals published between 2013 and 2025. The keywords used included “visionary leadership,” “teacher welfare,” “professional collaboration,” “work motivation,” and “learning innovation.” A total of 48 selected articles were analyzed using thematic synthesis techniques. The findings indicate that visionary leadership has a positive but predominantly indirect effect on teacher learning innovation. Three key mediating mechanisms were identified teacher welfare, encompassing financial and psychological well-being, which enhances teachers’ creative capacity; professional collaboration, such as learning communities and lesson study, which promotes knowledge sharing; and work motivation, both intrinsic and extrinsic, which sustains innovative practices. These three aspects operate synergistically in an integrated model. This study highlights that visionary leadership fosters innovation not through direct control but by creating supportive conditions. Its novelty lies in integrating teacher welfare, collaboration, and motivation as mediators. The findings contribute theoretically and practically by emphasizing a systemic approach to strengthening teacher learning innovation.